Multicultural Islamic Education as Strategy for Strengthening Social Cohesion in Islamic School - Muhammad Fahmi; Muhammad Adib Nuruzzaman; Masdar Hilmy; Hanik Yuni Alfiyah; Nadlir Nadlir; Nor Azni Abdul Aziz; Lilik Huriyah (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
Issues of social cohesion and interfaith tolerance are crucial in the context of diverse societies, including Bali, Indonesia, and Southern Thailand, which have experienced conflicts related to religious and cultural differences. This study aims to explore the role of multicultural Islamic education in strengthening social cohesion at Bali Bina Insani Islamic School (SI-BBI) and Phatnawitya School (PS). Utilizing a qualitative case study approach, this research employs in-depth interviews, participant observation, and documentation with school principals and teachers at both schools as primary data sources, which are then analyzed using descriptive-qualitative methods. The findings reveal that multicultural Islamic education at SI-BBI is implemented through the integration of local cultural values into the curriculum, such as the use of the Balinese language and the recruitment of Hindu teachers, as a form of acculturation that fosters social cohesion among the Muslim minority and Hindu majority in Bali. Meanwhile, at PS, multicultural Islamic education is applied with the inclusive principle of rahmatan lil alamin, incorporating cross-cultural learning and reinforcing tolerance values for students in the Muslim-majority but locally cultural region of Southern Thailand. These findings expand the understanding of Social Identity Theory from Henri Tajfel and John Turner, by demonstrating that multicultural education can reduce identity conflicts and strengthen social integration through learning that respects diversity. The implications of this research emphasize the need for educational policies that are friendly to religious and cultural diversity, which support the integration of multicultural values ​​in the education system in areas with potential for conflict. The multicultural Islamic education models in these two schools offer strategic frameworks for application in contexts of cultural and religious diversity, aiming to create sustainable social cohesion.